Echoes of Words Across Cultures: Advancing English Learning Through Literature in Kirkuk - Mohamedtahr, Mohammed Saher Mohamedtahr (Sulaimani Journal for Humanities, 2026)
This study examines the role of English literature in improving language education in Kirkuk's multicultural academics. Distinguished by its rich cultural and linguistic diversity, the city presents unique opportunities and challenges for instructors to balance global standards with local values. The study investigates how integrating literary works into English language academic programs can promote moral improvement, cultural understanding, and language proficiency, addressing the city's distinctive learning requirements. Literature is a powerful tool for teaching language and ethics, offering students revelation to universal concepts such as empathy, equity, and cultural diversity. By captivating with texts that reverberate with their experiences or introduce them to new perspectives, students can enhance their language proficiency while developing a deeper appreciation of moral and cultural nuances. For example, novels and stories that deal with issues of identity and coexistence establish a space for discussions on moral values and social harmony, making literature an active educational resource in Kirkuk's multicultural classrooms. The study also examines instructors' challenges in applying literature-based language programs in such a diverse community. These include addressing different levels of English proficiency and incorporating ethical and cultural content without subverting local traditions. Finally, this research advocates for a curriculum that includes the two-sided role of literature in developing language skills and instilling moral principles. The findings guide instructors in creating an embracing and effective model for English language education, potentially stimulating similar efforts in other multicultural environments.
Keywords: Kirkuk; literature based language; multicultural academics; linguistic diversity; cultural diversity